THE CHILD’S RIGHT TO MAINTAIN CONTACT WITH BOTH PARENTS IN THE AGE OF PANDEMIC (EU and comparative law issues and challenges series (ECLIC), 2021)
The COVID-19 pandemic and the accompanying extraordinary measures engaged restrictions of fundamental human rights and liberties to an unprecedented scale. Inevitably, this had implications in the family context as well. Even though children are not considered to be an endangered category from a medical perspective, they are adversely affected by the pandemic in practically all aspects of life, in the short-term and in the long-term. One of the child’s rights directly affected is the right to maintain direct contact with both parents on a regular basis. Digital means of communication can somewhat mitigate the lack of personal contact, however, not everyone has access to the necessary technologies and there might be various disagreements about exercising such indirect contact. The closure of judiciary and social services placed the burden of resolving contact related disputes almost entirely upon parents. This paper aims to examine the relevant legal framework and measures taken in relation to the child’s right to maintain contact with both parents in the circumstances of the pandemic, with particular focus on the Croatian context and the response of the Croatian authorities to the challenges arising from this extraordinary situation, and to identify actions which could be taken in order to improve the child’s unfavourable position.